2020
DOI: 10.1002/aah.10118
|View full text |Cite
|
Sign up to set email alerts
|

Hematology and Clinical Biochemistry Profiles in Antillean Manatee Trichechus manatus manatus from Different Types of Captivity and Free Living in Northeast Brazil

Abstract: The Antillean manatee Trichechus manatus manatus can be found along the northern and northeastern coasts of Brazil. Previous studies on the clinical biochemistry of these animals were conducted in North America and the Caribbean, whereas little is known regarding these parameters in South American manatee populations. Accordingly, the objective of the present study was to examine the hematology and clinical biochemistry of Antillean manatees of different sexes and from different environments in northeast Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
4
5
0
Order By: Relevance
“…Erythrocyte and total leukocyte counts measured in this study were similar to those previously reported for manatees in Guyana, Mexico, Belize, Brazil, and Florida [ 6 9 , 14 , 25 ] ( Table 6 ). Red blood cell count was highest in neonates (>3.0 × 10 6 /mm 3 ) and decreased as manatees grew and learned to dive [ 6 , 32 ], as evident in significant variation among age classes observed in the study ( Table 2 ).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Erythrocyte and total leukocyte counts measured in this study were similar to those previously reported for manatees in Guyana, Mexico, Belize, Brazil, and Florida [ 6 9 , 14 , 25 ] ( Table 6 ). Red blood cell count was highest in neonates (>3.0 × 10 6 /mm 3 ) and decreased as manatees grew and learned to dive [ 6 , 32 ], as evident in significant variation among age classes observed in the study ( Table 2 ).…”
Section: Discussionsupporting
confidence: 89%
“…Aspartate aminotransferase appears to be of little or no clinical value in manatees [6]. However, values for Puerto Rico were comparable to those described for Florida [6,24], Guyana [7], and Brazil [14] but lower than in Mexico and Belize [8,9]. Increased alkaline phosphatase may be present in growing, young mammals in some terrestrial species associated with osteoblastic activity [36], as seen in our reference ranges of Puerto Rican manatee calves versus adults.…”
Section: Muscle-associatedsupporting
confidence: 71%
See 3 more Smart Citations